Use It or Lose It: Irish Evidence - Irene Mosca; Robert E. Wright (Institute for the Study of Labor (IZA), 2016)
A small but growing body of research suggests that retirement and cognitive decline are related. In fact, some have argued that retirement causes cognitive decline. The aim of this paper is to add to this literature using data of older women from The Irish Longitudinal Study on Ageing (TILDA). Ordinary least square (OLS) regressions show a significant negative association between retirement and cognitive functioning. These estimates are based on the assumption that retirement is exogenous. As retirement is potentially endogenous with respect to cognition, instrumental variable (IV) methods are also used. The instrument employed is the abolition of the so-called "Marriage Bar". In simple terms, the Marriage Bar was the requirement that women leave paid employment on getting married. It was established in the 1930s and removed in the 1970s. When IV estimations are used, the effect of retirement on cognition is negative but statistically insignificant. Differences between OLS and IV estimates are compared with a standard test. OLS estimates are preferred as the null hypothesis of exogeneity of retirement cannot be rejected at conventional statistical levels.
Keywords: J14; J26; 330; cognition; ageing; retirement